Pengaruh Pandemi Covid 19 Terhadap Permintaan Pasar Sasirangan Pada UMKM Di Kota Banjarmasin Kalimantan Selatan (Studi Kasus UMKM Muslim) - Dewi Maharani (ITB AAS INDONESIA Surakarta, 2021)
The COVID-19 pandemic has had many economic, social, and political impacts not only on large countries but almost all countries in the world. Indonesia is one of the countries experiencing the economic impact of the Covid 19 pandemic from all sectors. One of them is the Sasirangan cloth SMEs in the city of Banjarmasin, South Kalimantan. MSMEs in Indonesia dominate, therefore the Government must pay special attention to MSMEs that have been impacted during the Covid-19 pandemic in order to survive in a pandemic situation. This study aims to measure the magnitude of the impact that occurs on Sasirangan cloth SMEs in the city of Banjarmasin, especially Muslim MSMEs in terms of market demand for sasirangan cloth. So that researchers are able to analyze the role of the Government in helping SMEs of sasirangan cloth to survive and measure the extent to which innovations made by SMEs of sasirangan cloth during the pandemic to continue their business journey during the pandemic. Innovations made by SMEs of sasirangan cloth can later be consumed during or after the pandemic.